Long-term (2003–2018) trends in aerosol chemical components at a high-altitude background station in the western North Pacific: Impact of long-range transport from continental Asia. (October 2020) - Singh, Atinderpal; Chou, Charles C.-K.; Chang, Shih-Yu; Chang, Shuenn-Chin; Lin, Neng-Huei; Chuang, Ming-Tung; Pani, Shantanu Kumar; Chi, Kai Hsien; Huang, Chiu-Hua; Lee, Chung-Te
Abstract: This study examined the long-term trends in chemical components in PM2.5 (particulate matter with aerodynamic diameter ≤2.5 μm) samples collected at Lulin Atmospheric Background Station (LABS) located on the summit of Mt. Lulin (2862 m above mean sea level) in Taiwan in the western North Pacific during 2003–2018. High ambient concentrations of PM2.5 and its chemical components were observed during March and April every year. This enhancement was primarily associated with the long-range transport of biomass burning (BB) smoke emissions from Indochina, as revealed from cluster analysis of backward air mass trajectories. The decreasing trends in ambient concentrations of organic carbon (−0.67% yr −1 ; p  = 0.01), elemental carbon (−0.48% yr −1 ; p  = 0.18), and non–sea-salt (nss) K + (−0.71% yr −1 ; p  = 0.04) during 2003–2018 indicated a declining effect of transported BB aerosol over the western North Pacific. These findings were supported by the decreasing trend in levoglucosan (−0.26% yr −1 ; p  = 0.20) during the period affected by the long-range transport of BB aerosol. However, NO3 − displayed an increasing trend (0.71% yr −1 ; p  = 0.003) with considerable enhancement resulting from the air masses transported from the Asian continent. Given that the decreasing trends were for the majority of the chemical components, the columnar aerosol optical depth (AOD) also demonstrated a decreasing trend (−1.04% yr −1 ; p  = 0.0001) during 2006–2018. Overall decreasing trends in ambient (carbonaceous aerosol and nss-K + ) as well as columnar (e.g., AOD) aerosol loadings at the LABS may influence the regional climate, which warrants further investigations. This study provides an improved understanding of the long-term trends in PM2.5 chemical components over the western North Pacific, and the results would be highly useful in model simulations for evaluating the effects of BB transport on an area. Graphical abstract: Image 1 Highlights: Biomass burning smoke transported from Indochina influenced East Asia in spring. Carbonaceous aerosol and nss-K + exhibited a decreasing trend over the study region. The transport of anthropogenic aerosol from Indochina displayed an increasing trend. Declining in transported biomass burning aerosol was observed in the study region.